The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1294/jes.30.25
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective comparison of induction with thiopental/guaifenesin and propofol/ketamine in Thoroughbred racehorses anesthetized with sevoflurane and medetomidine during arthroscopic surgery

Abstract: This study compares clinical characteristics between induction with thiopental/guaifenesin and propofol/ketamine in Thoroughbred racehorses anesthetized with sevoflurane and medetomidine. Clinical records of 214 horses that underwent arthroscopic surgery between 2015 and 2016 were retrospectively retrieved. Horses were premedicated with medetomidine and midazolam to sedate at the adequate level for smooth induction, and then induced with either thiopental (4.0 mg/kg) and guaifenesin (100 mg/kg) in Group TG (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…This was corroborated by another study which found that S‐ketamine provided quieter and more controlled recoveries 32 . Administration of propofol and ketamine for induction of anaesthesia resulted in shorter recovery times and better QR compared to thiopental and guaifenesin 140 . In both groups a good QR was noted, therefore, despite the results showing a statistically significant difference, they might be clinically irrelevant.…”
Section: Resultsmentioning
confidence: 60%
“…This was corroborated by another study which found that S‐ketamine provided quieter and more controlled recoveries 32 . Administration of propofol and ketamine for induction of anaesthesia resulted in shorter recovery times and better QR compared to thiopental and guaifenesin 140 . In both groups a good QR was noted, therefore, despite the results showing a statistically significant difference, they might be clinically irrelevant.…”
Section: Resultsmentioning
confidence: 60%
“…The individual doses of ketamine and propofol used in this report are similar or lower than the previously reported in the literature, with recommendations for ketamine at 2 mg/kg with diazepam after xylazine premedication, 2 or propofol at 2-6 mg/kg when used alone in foals. 9,20 The ketofol doses chosen for these cases were based on similar ratios reported in horses 10,19,21 and dogs 13 which showed smooth inductions and recoveries. There are limited pharmacokinetic studies for propofol in foals.…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, recovery from general anaesthesia was rapid and of good quality, despite the administration of a propofol top‐up and xylazine in cases 1 and 2, respectively. Similarly, in adult horses, superior recoveries and fewer attempts to standing were also reported using ketamine‐propofol inductions instead of thiopentone guaifenesin 21 and ketamine‐midazolam, 10 respectively. In children, the median recovery time for ketofol was found to be faster than with intravenous ketamine, but longer than when propofol was used alone 14 .…”
mentioning
confidence: 94%
“…Ketamine is the most frequent agent used to induce general anaesthesia in horses [1,70]. Ketamine is superior to thiopental and the mixture tiletamine/zolazepam regarding duration and quality of recovery [94,98,104,109,110,122]. Thiopental might be still used as an alternative in ocular patients to avoid increases in intraocular pressures [102].…”
Section: Premedication/sedation and Induction Drugsmentioning
confidence: 99%